Routines’ errors when solving mathematics problems cause cognitive conflict - Enditiyas Pratiwi; Toto Nusantara; Susiswo Susiswo; Makbul Muksar (Institute of Advanced Engineering and Science, 2022)
Many studies showed that cognitive conflict often occurs in learning and when solving mathematics problems. However, very few studies have looked at cognitive conflicts in solving mathematics problems, incredibly improper fraction problems. This descriptive qualitative study described and analyzed students’ errors in solving mathematics problems using a commognitive perspective. The data was collected using a test sheet instrument, where students do the test think-aloud. The answers on the student test sheets were analyzed by adjusting the think-aloud that was carried out, and then the interview process was carried out as a form of triangulation of the method in the study. The data analysis results showed that there was a routine error that causes cognitive conflict when solving the improper fraction problem. The error that occurred indicates that the routine can and cannot resolve the cognitive conflict that occurs. This study’s findings indicated the importance of routine procedures to be understood so that their use is appropriate for solving mathematical problems.